Dietary bioactive compounds for type 2 diabetes: A comprehensive review of molecular interactions and mechanistic insights - Oumayma Aguerd; Hamza Elhrech; Meryem El Fessikh; Khan Wen Goh; Nasreddine El Omari; Tarik Aanniz; Abdelhakim Bouyahya (Journal of Functional Foods, 2025)
Diabetes mellitus (DM) is a prevalent, long-term illness that adversely impacts patients' quality of life and significantly increases the risk of severe complications. Type 2 diabetes mellitus (T2DM) accounts for approximately 90 % of global diabetes cases and is influenced by lifestyle and epigenetic factors, including dietary habits and physical inactivity. Current primary treatments involve lifestyle changes and synthetic medications, which, despite their efficacy, can result in adverse side effects and high costs. In response, there is growing interest in plant-derived bioactive compounds as alternative therapeutic options for T2DM, given their accessibility, lower cost, and reduced risk of side effects. This review comprehensively explores the pharmacological actions of natural compounds against key molecular targets implicated in T2DM pathology, such as dipeptidyl peptidase-4 (DPP4), α-amylase, α-glucosidase, peroxisome proliferator-activated receptor γ (PPARγ), protein tyrosine phosphatase-1B (PTP1B), and glucose transporter type-4 (GLUT4), along with their roles in mitigating lipotoxicity and glucotoxicity. These findings underscore the potential of bioactive compounds in developing safer and more effective T2DM management strategies, paving the way for further research and clinical trials.